On the Performance of Angular Diversity Receivers in Underground Mining Vlc Systems - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2022)
Visible Light Communications (VLC) have generated great interest in the scientific community in the last five years due to their great adaptation to harsh environments. Among the scenarios that can benefit from the advantages of VLC systems are Underground Mining (UM) tunnels. However, the physical phenomena and the irregularity of this environment present a challenge for the implementation of the systems called UM-VLC. Therefore, it is important to research and develop practical solutions that improve the performance of these systems in the UM scenario and verify their efficiency. Under this context, in this article we propose the implementation of pyramidal and hemi-dodecahedral Angle Diversity Receivers (ADRs) in the reception stage of a UM-VLC system. These solutions, along with the Maximum Ratio Combining (MRC) signal selection scheme, are evaluated and compared in terms of User Data Rate (UDR) and Cumulative Distribution Function (CDF) with respect to the Signal-to-Interference-plus-Noise Ratio (SINR). The numerical results obtained through computational simulations show that the hemi-dodecahedral ADR outperforms the the pyramidal ADR in terms of the evaluated metrics. © 2022 IEEE.